Recent advances in synthetic biology of cyanobacteria for improved chemicals production. Issue 1 (1st January 2020) - Wang, Fen; Gao, Yuanyuan; Yang, Guang
ABSTRACT: Cyanobacteria are Gram-negative photoautotrophic prokaryotes and have shown great importance to the Earth's ecology. Based on their capability in oxygenic photosynthesis and genetic merits, they can be engineered as microbial chassis for direct conversion of carbon dioxide to value-added biofuels and chemicals. In the last decades, attempts have given to the application of synthetic biology tools and approaches in the development of cyanobacterial cell factories. Despite the successful proof-of-principle studies, large-scale application is still a technical challenge due to low yields of bioproducts. Therefore, recent efforts are underway to characterize and develop genetic regulatory parts and strategies for the synthetic biology applications in cyanobacteria. In this review, we present the recent advancements and application in cyanobacterial synthetic biology toolboxes. We also discuss the limitations and future perspectives for using such novel tools in cyanobacterial biotechnology. Graphical abstract: